Inferring Tax Compliance from Pass-through: Evidence from Airbnb Tax Enforcement Agreements - Andrew J. Bibler; Keith F. Teltser; Mark J. Tremblay (Center for Economic Studies and ifo Institute (CESifo), 2019)
Tax enforcement can be prohibitively costly when market transactions and participants are difficult to observe. Evasion among market participants may reduce tax revenue and provide certain types of suppliers an undue competitive advantage. Whether efforts to fully enforce taxes are worthwhile depends on the rate of compliance in the absence of such efforts. In this paper, we show that an upper bound on pre-enforcement tax compliance can be obtained using market data on pre- and post-enforcement periods. To do this, we estimate the pass-through of tax enforcement agreements between Airbnb and state and local governments, which achieve full compliance at the point of sale. Using data on Airbnb listings across a number of U.S. metropolitan areas, as well as variation in enforcement agreements across time, location, and tax rate, we estimate that taxes are paid on no more than 24 percent of Airbnb transactions prior to enforcement. We also find that demand is inelastic, which drives several key insights: the economic burden of taxation disproportionately falls on renters, excess burden is very small, and tax enforcement is not an effective policy lever for interest groups seeking to reduce local Airbnb activity.
Keywords: H20; H22; H26; L10; 330; evasion; short-term housing rentals; sharing economy; voluntary collection agreements; online sales and use taxes